Amines as effective ligands in iridium-catalyzed decarbonylative dehydration of biosourced substrates. Issue 15 (16th July 2018) - Ternel, Jérémy; Léger, Bastien; Monflier, Eric; Hapiot, Frédéric
Abstract : Linear α-olefins (LAOs) and linear internal olefins (LIOs) are essential intermediates in the synthesis of surfactants, lubricants, and polymers. Abstract : Linear α-olefins (LAOs) and linear internal olefins (LIOs) are essential intermediates in the synthesis of surfactants, lubricants, and polymers. Concurrently with petroleum-based industrial processes, the production of LAOs and LIOs from renewable feedstocks has gained increasing interest in recent years. Organometallic catalysts have been developed designedly, especially Pd, Fe and Ir catalysts. However, such catalysts are mostly stabilized by phosphanes, ligands sometimes difficult to handle especially on large scales. Alternatives to phosphanes would thus be highly desirable. In the present study, we demonstrate that Ir catalysts coordinated by amines are suitable to decarbonylate a wide range of biosourced substrates under mild conditions. The resulting LAOs and LIOs are obtained with good conversion provided that the nature and the quantity of the amines are controlled accurately. The LAO/LIO selectivity can also be tuned by a judicious choice of experimental conditions. Interestingly, the Ir-based catalytic system is applicable to the decarbonylative dehydration of saturated, unsaturated and polyunsaturated fatty acids.